Forecasting financial liabilities for accrued Ordinary vacations benefits in accordance with IAS19 requirements - Abdalrahman Ibrahim Khashaa / Sallama Ibrahim Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The research aims to clarify the predictive procedures necessary to predict the financial obligation for the accumulated leave allowance paid to employees after their referral to retirement, by relying on the local laws and legislation in question and in accordance with the requirements of the IAS19 standard, by displaying and categorizing the regular leave benefits provided to employees, as well as predicting the financial obligation for the benefits. The accumulated regular leave allowance is in accordance with the requirements of the international IAS19 standard, due to the absence of predictive procedures for this type of benefits provided to employees in Iraqi economic units, which may cause a delay in the payment of that obligation. The researchers relied on a basic hypothesis that says, “There is no possibility to predict the financial obligation for the allowance.” Regular leaves accumulated in local economic units in accordance with the requirements of the IAS19 standard. The research sample was represented by a group of employees of the General Company for Baghdad Electricity Distribution/ Karkh Electricity Distribution Branch who are supposed to be referred to retirement during the next year if they will enter the legal age for referral to retirement (60) years. The most prominent finding of the two researchers is that forecasting accumulated leave allowance obligations leads to providing useful information in preparing plans and making decisions. The forecasting process for the accumulated regular leave allowance obligation can be carried out by relying on current information appropriate to the employees of the research sample unit with the possibility of arriving at results close to reality. The researchers also stressed the need to intensify training courses and workshops for human resources and payroll employees in economic units to gain knowledge in how to apply The requirements of international accounting standards, especially the IAS19 employee benefits standard, as well as the use of electronic systems that work to make predictions regarding the accumulated leave allowance obligation, which facilitates knowing the size of the obligation that must be paid for the entitlement. The researchers also suggest the need for local economic units to carry out forecasting operations in a manner annually regarding the accumulated leave allowance provided to its employees in order to secure it on the due date.